2018
DOI: 10.5137/1019-5149.jtn.21835-17.3
|View full text |Cite
|
Sign up to set email alerts
|

The geometry of the circle of willis anatomical variants as a potential cerebrovascular risk factor

Abstract: We described anatomical variants of both the anterior and posterior circulations and their specific effects on the hemodynamic balance of cerebral blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 20 publications
(40 reference statements)
2
40
0
Order By: Relevance
“…Experimental and computational models suggest that increased flow through an abnormal configuration of patent branches increases wall sheer stress leading to aneurysmal formation. [1][2][3][4] Similarly, incomplete configuration increases the risk of ischemic stroke, likely due to reduced collateral circulation. [4,5] An incomplete CoW as a risk factor for stroke and aneurysm formation continues to be a focus of research in cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and computational models suggest that increased flow through an abnormal configuration of patent branches increases wall sheer stress leading to aneurysmal formation. [1][2][3][4] Similarly, incomplete configuration increases the risk of ischemic stroke, likely due to reduced collateral circulation. [4,5] An incomplete CoW as a risk factor for stroke and aneurysm formation continues to be a focus of research in cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Similarly, incomplete configuration increases the risk of ischemic stroke, likely due to reduced collateral circulation. [4,5] An incomplete CoW as a risk factor for stroke and aneurysm formation continues to be a focus of research in cerebrovascular disease. In 1984, Kayembe et al [6] found aneurysms to be more common in autopsy studies in patients with CoW anatomic variations, a finding suggested by CoW assessment with advanced imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistent results on whether a complete CoW may be protective against WMH may hint of a more complex role of the CoW in the cerebrovascular system than just having the role as a compensatory system in case of arterial occlusion. This has been suggested by previous studies (Pascalau et al, 2018;Vrselja et al, 2014). In particular, Vrselja et al argued that the CoW also plays a role in blood pressure dissipation, ensuring lower fluctuations in blood pressure in the downstream cerebral arteries of the CoW (Vrselja et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…"is there a general vulnerability in the right MCA area for ischemia", mechanistic simulations might be able to provide this information instead of direct perfusion measurements. Also, since many variants of the CoW exist, the simulation could allow the identification of patients with high-risk for stroke owing to their individual CoW configuration (Pascalau et al 2018).…”
Section: Discussionmentioning
confidence: 99%